Customer Satisfaction Analysis Viewed From Store Atmosphere, Food Plating And Price Perception (Survey of Letter Coffee Consumers) - Soni Setiaji Setiaji; Depy Muhamad Pauzy; Mila Karmila (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of Store Atmosphere, Food Plating and Price Perceptions on Letter Coffee Consumer Satisfaction in Cijoho, Kec. Leuwisari, Tasikmalaya Regency. The research method used is a quantitative method with a survey approach of 100 respondents who are consumers of Letter Coffee. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that Store Atmosphere, Food Plating and Price Perception have a significant effect both partially and simultaneously on Letter Coffee Consumer Satisfaction in Cijoho, Kec. Leuwisari, Tasikmalaya Regency.